Beneath the sea in 3-D - Blum, Mark (Chronicle Books, 1997)
Dive into the world's most exotic waters without even getting wet! This amazing collection of stereoscopic photographs brings to life the spectacular creatures of the deep like never before. A truly foolproof 3-D experience, Beneath the Sea in 3-D is complete with lenses innovatively bound in the hardback cover at precisely the right viewing distance to allow you to go 'inside the photograph' and perceive depth and detail far beyond the ability of normal human vision. See eye-to-eye with a luminescent angelfish, go one-on-one with a lively shrimp, and swim surprisingly close to an ethereal jellyfish.